Análise das transações dos pequenos produtores hortícolas da região Serrana do estado do Rio de Janeiro - Mozambani, Carlos Ivan (Universidade Federal de São Carlos, 2017)
The objective this research is to identify and describe the main governance structures adopted by small farmers in Serrana region of the state of Rio de Janeiro, as well as to determine the factors that explain the adoption of these structures. The theoretical basis used was the Transaction Cost Economics. The method used was exploratory quantitative, with a survey containing 262 small farmer. These were statistically selected from lists of producers supplied by unions in each of the 7 cities in the region. A structured questionnaire was applied so that 567 transactions involving vegetables were identified. An indicator of coordination intensity was constructed to identify the governance structures adopted in such transactions. Four different groups of coordination intensity were formed, allowing comparative analysis using descriptive statistic. It follows an estimation of an ordered logit regression in order to idenfy factors explaining the four groups of coordination intensity. There is evidence of the predominance of hybrid forms of governance in transactions involving small farmers with their buyers. The high level of physical specificity and / or intermediate levels of human specificity were statistically significant as determinant factors explaining the adoption of governance structures with greater coordination intensity. The size of the property under management of horticulturists was also significant, however, in this case, larger farmers showed a greater probability of adopting structures with less intensity of coordination. The presence of resource sharing among these agents promotes commitment among the parties, generating an informal mechanism in the transaction and differentiating them from the traditional spot market. Buyers have developed good reputation, generating trust-based commitments.
Keywords: Agricultura familiar; Horticultura; Coordenação; Transação; Small farmers; Horticulture; Coordination; Transactions; ENGENHARIAS::ENGENHARIA DE PRODUCAO